2017
DOI: 10.7860/jcdr/2017/30138.10327
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Epidermal Growth Factor Receptor in Patients of Glioblastoma Multiforme

Abstract: EGFR negative patients respond better to therapy along with longer duration of survival as compared to EGFR positive patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
3
13
2
Order By: Relevance
“…Despite the low prevalence of this tumor, it accounts for 2.5% of cancer deaths [12] and the survival of patients is 3 months, but treatment leads to higher survival of these patients. Recently, studies have shown that patients with EGFR mutations have responded appropriately to targeted therapy [11]. In our study, the Mean±SD overall survival of patients was 22.3±2.5 months.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Despite the low prevalence of this tumor, it accounts for 2.5% of cancer deaths [12] and the survival of patients is 3 months, but treatment leads to higher survival of these patients. Recently, studies have shown that patients with EGFR mutations have responded appropriately to targeted therapy [11]. In our study, the Mean±SD overall survival of patients was 22.3±2.5 months.…”
Section: Discussionsupporting
confidence: 50%
“…The study by Smith et al has found no association between the expression of EGFR with prognosis and survival rate [10]. However, Tripathy et al, have found a significant correlation between the expression of EGFR and survival time [11]. Considering that in previous studies, different results have been reported in terms of EGFR expression and survival rate of patients with GBM, we decided to investigate EGFR expression and its relationship with demographic and prognostic variables and patient survival.…”
Section: Introductionmentioning
confidence: 96%
“…Genomic analysis suggests survival-related genomic abnormalities in GBM patients, such as epidermal growth factor receptor (EGFR) amplification [12, 13] and isocitrate dehydrogenase 1/2 (IDH1/2) mutations [14, 15], have prognostic value. Some studies show that high expression of EGFR indicated poor prognosis [16], and other research find the IDH mutations are associated with improved survival [17]. From the epigenetic level, O -6-methylguanine-DNA methyltransferase (MGMT) promoter methylation has been demonstrated that it is associated with improved progression-free and overall survival in GBM patients treated with alkylating agents [18].…”
Section: Introductionmentioning
confidence: 99%
“…Backflow-free catheters are under evaluation to increase the flow rates at higher values to mitigate this phenomenon [84]. CED was investigated for the delivery of various agents, such as conventional chemotherapy [86], cytotoxin-ligand conjugates targeting cell surface receptors [87], antisense oligonucleotides [86,88], and nanovectors [86,89]. CED showed promising results when used to infuse brain-penetrating nanoparticles (BPNP) that resulted in significant tissue penetration thanks to their small size and their stability as monodispersed agents and allowed for drug release in a controlled fashion.…”
Section: Bypassing the Bbbmentioning
confidence: 99%